Thiouracil-Forming Bacteria Identified and Characterized upon Porcine In Vitro Digestion of Brassicaceae Feed - Kiebooms, Julie A. L. (Appl Environ Microbiol, 2014)
In recent years, the frequent detection of the banned thyreostat thiouracil (TU) in livestock urine has been related to endogenous TU formation following digestion of glucosinolate-rich Brassicaceae crops. Recently, it was demonstrated that, upon in vitro digestion of Brassicaceae, fecal bacteria induce TU detection in livestock (porcine livestock > bovines). Therefore, the present study was intended to isolate and identify bacteria involved in this intestinal TU formation upon Brassicaceae digestion and to gain more insight into the underlying mechanism in porcine livestock. Twenty porcine fecal inocula (gilts and multiparous sows) were assessed through static in vitro colonic-digestion simulations with rapeseed. After derivatization and extraction of the fecal suspensions, TU was analyzed using liquid chromatography-tandem mass spectrometry (LC-MS(2)). On average, lower TU concentrations were observed in fecal colonic simulations in gilts (8.35 ng g(−1) rapeseed ± 3.42 [mean ± standard deviation]) than in multiparous sows (52.63 ng g(−1) ± 16.17), which correlates with maturation of the gut microbial population with age. Further exploration of the mechanism showed cell-dependent activity of the microbial conversion and sustained TU-forming activity after subjection of the fecal inoculum to moderate heat over a time span of up to 30 min. Finally, nine TU-producing bacterial species were successfully isolated and identified by a combination of biochemical and molecular techniques as Escherichia coli (n = 5), Lactobacillus reuteri (n = 2), Enterococcus faecium (n = 1), and Salmonella enterica subsp. arizonae (n = 1). This report demonstrates that endogenous formation of TU is Brassicaceae induced and occurs under colonic conditions most likely through myrosinase-like enzyme activity expressed by different common intestinal bacterial species.